The Incoherence of Orientalist Methodologies and Their Westernized Followers in the Study of the Qur’an and Its Sciences - Dr. Yousef Moussa Ali Abdullah Abu Aliqa (Journal of Scientific and Human Dimensions, 2026)
This research presents a methodological critique of Western Orientalists’ approaches to the study of the Qur’an and its sciences. Although their methods vary in tools and techniques, they converge on a single objective: to cast doubt on Islamic belief, limit the spread of Islam, and weaken its authentic civilization and intellectual foundations. Some Orientalists attempted to portray Islam as fragmented into separate religions—such as the Islam of the Sufis, the Islam of the jurists, and political Islam—in an effort to dismantle the unity of creed and strip it of its spiritual and moral substance. Others sought to trace Islam back to external Jewish or Christian origins in order to argue that the Qur’an is of human authorship, leading to the formation of a distorted image of Islam in Western consciousness. The danger of these methodologies lies in their reliance on the so called “influence and borrowing” theory, which asserts that the Qur’anic text was influenced by earlier religious traditions, without adhering to scientific research standards or observing objectivity and intellectual neutrality.